2018
DOI: 10.1093/nar/gky597
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma brucei UMSBP2 is a single-stranded telomeric DNA binding protein essential for chromosome end protection

Abstract: Universal minicircle sequence binding proteins (UMSBPs) are CCHC-type zinc-finger proteins that bind a single-stranded G-rich sequence, UMS, conserved at the replication origins of the mitochondrial (kinetoplast) DNA of trypanosomatids. Here, we report that Trypanosoma brucei TbUMSBP2, which has been previously proposed to function in the replication and segregation of the mitochondrial DNA, colocalizes with telomeres at the nucleus and is essential for their structure, protection and function. Knockdown of Tb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 78 publications
0
18
0
Order By: Relevance
“…Expression of recombinant GST‐tagged DRBD18 was carried out as described earlier (Lott et al., 2015). For His‐Mtr2 (Tb927.7.5760), the ORF was cloned into the MCS‐1 of pETDuet‐1vector (with MSC2 left empty), with frameshift correction by insertion of single nucleotide before the start codon (Kafková et al., 2017) and was purified using immobilized metal affinity chromatography (IMAC) as described earlier (Klebanov‐Akopyan et al., 2018). For GST pulldown assays, all recombinant plasmids including pGEX4T‐1, were transformed into E .…”
Section: Methodsmentioning
confidence: 99%
“…Expression of recombinant GST‐tagged DRBD18 was carried out as described earlier (Lott et al., 2015). For His‐Mtr2 (Tb927.7.5760), the ORF was cloned into the MCS‐1 of pETDuet‐1vector (with MSC2 left empty), with frameshift correction by insertion of single nucleotide before the start codon (Kafková et al., 2017) and was purified using immobilized metal affinity chromatography (IMAC) as described earlier (Klebanov‐Akopyan et al., 2018). For GST pulldown assays, all recombinant plasmids including pGEX4T‐1, were transformed into E .…”
Section: Methodsmentioning
confidence: 99%
“…Expression of recombinant GST-tagged DRBD18 was carried out as described earlier (Lott et al, 2015). For His-Mtr2 (Tb927.7.5760), the ORF was cloned into the MCS-1 of pETDuet-1vector (with MSC2 left empty), with frame shift correction by insertion of single nucleotide before the start codon (Kafková et al, 2017) and was purified using immobilized metal affinity chromatography (IMAC) as described earlier (Klebanov-Akopyan et al, 2018). For GST pulldown assays, all recombinant plasmids including pGEX4T-1, were transformed into Escherichia coli BL21 strain, and protein expression was induced by addition of 0.5 mM isopropyl 1-thio-Dgalactopyranoside (IPTG) and subsequent growth at 22°C overnight.…”
Section: Protein Expression and Gst Pulldown Assaymentioning
confidence: 99%
“…Recently, it was shown that T. brucei UMSBP2, which is involved in kDNA replication and segregation, is also localized at telomeres. The RNAi system showed that this protein not only participates in nuclear division but also plays a role in the coordinated replication of DNA-containing organelles 65 .…”
Section: Discussionmentioning
confidence: 99%